Primary Histoplasma capsulatum Enterocolitis Mimicking Peptic and Inflammatory Bowel Disease - Rahman Nakshabendi; Andrew C. Berry; Daisy Torres-Miranda; Francis Daniel LaBarbera; Ozdemir Kanar; Ahmad Nakshabandi; Imad Nakshabendi (Case Reports in Gastrointestinal Medicine)
In immunocompromised patients, histoplasmosis may present as disseminated disease. We present a 52-year-old Caucasian male with symptoms of dyspepsia, postprandial epigastric pain, nausea, and nonbloody diarrhea. Upper and lower gastrointestinal endoscopies were suspicious for inflammatory bowel disease (IBD); however, biopsies were consistent with histoplasmosis, specifically in the duodenum.